Protective or harmful? Exploring the ambivalent role of social identification as a moderator of intergroup stress in sojourners - Bierwiaczonek, K. (2018)
Living outside one's home country may be stressful, and having strong social ties should help deal with this stress. However, social ties may be protective or harmful depending on whether the social group they evoke belongs to the host- or the home country context. The current study examines how social identification with different groups may either buffer or aggravate the negative effects of two stressors (perceived discrimination and symbolic threat) on sojourner adaptation. Two hundred and twenty international students sojourning in nine different countries responded to an online questionnaire. As expected, adaptation was negatively predicted by both stressors. Moreover, high identification with the group of international students attenuated the negative effects of perceived discrimination on psychological adaptation, while home country identification aggravated the negative effects of symbolic threat on sociocultural adaptation.